Strategi Optimalisasi Pendapatan Asli Daerah : Analisis SWOC terhadap Rencana Strategi (Renstra) Badan Pendapatan Daerah Kota Kupang Tahun 2023-2026 - Pattimau, Andrianus; Wike, Wike; Sentanu, I Gede Eko Putra Sri (Jurnal Ilmiah Administrasi Publik, 2025)
This study aims to analyze strategies for optimizing Local Own-Source Revenue  in the Kupang City Government using a SWOC (Strengths, Weaknesses, Opportunities, Challenges) analysis of the Strategic Plan of the Regional Revenue Agency for the period 2023–2026.The research method used is a qualitatative approach with a descriptive type, while the main focus of the research is on analyzing the strategic plan document of the Kupang City Regional Revenue Agency to evaluate the strategic plan in increasing Local Own-SourceRevenue especially local tax.The analysis reveals that despite strengths such as an online tax system and qualified human resources, there are weaknesses including suboptimal regulations, limited budget, and lack of integrated technology. Opportunities such as the delegation of tax authority and stakeholder support should be leveraged to enhance  Local Own-Source Revenue. Key challenges include low taxpayer awareness and socio-political issues. The study recommends strengthening regulations, improving human resource capacity, advancing tax digitalization, and fostering inter-agency collaboration as primary strategies to sustainably increase  Local Own-Source Revenue.